Analisis Penerapan K3 Pada Pembelajaran Praktek Di Bengkel Mesin Politeknik TEDC - Nunik Ekawandani; Suharto Suharto (STIKes Surya Global Yogyakarta, 2020)
ABSTRACTBackground: Vocational college is one of the colleges that prepares students to become people who are ready to work or as people who can open their own jobs. Vocational learning prioritizes practice compared to theory, so that practical credits are greater than theory. With such conditions requires attention to health and safety during work practice workshops, workshops or laboratories. Because the cause of accidents is due to unsafe environmental conditions and unsafe behavior. Students as actors in this practice are the first priority in occupational health and safety. This Study aims to occupational health and safety.Methods:The method used in this research was a description by distributing questionnaires to students. Results: From the results of distributing questionnaires, it was found that students did not understand the general K3 knowledge. Students' knowledge of K3 generally showed good results for students majoring in machines who did not understand K3. Likewise with the use of PPE in practical learning, the average student has shown good results.Conslusion: The results of data analysis from this questionnaire serve as a basic reference for institutions to further improve their K3 facilities and equipment.Keywords: vocational, practice, occupational health and safety